A first principles study of the mechanical properties of Li–Sn alloys. Issue 45 (20th May 2015) - Zhang, Panpan; Ma, Zengsheng; Wang, Yan; Zou, Youlan; Lei, Weixin; Pan, Yong; Lu, Chunsheng
<x xml:space="preserve">Abstract</x> Focusing on the failure mechanism of active materials during charging–discharging, the mechanical properties of Li–Sn alloys are studied by density functional theory, including elastic moduli, Poisson's ratio, anisotropy, and brittleness-ductility.